FORMULATION OF GREEN DEMULSIFIER FOR WATER-INCRUDE OIL EMULSIONS - ADEYEMI,, BAMIKOLE JOSHUA (2015)
Chemical treatment is the most common method for resolving water-in-crude oil emulsions due to its many advantages. However, most conventional chemical demulsifiers are expensive, toxic and non-biodegradable, and have been listed among hazardous oilfield chemicals. Thus, the formulation of effective eco-friendly demulsifiers from Malaysia's local materials was the focus of this work. The study investigated the kinetics of stability of water-in-crude oil emulsions and their destabilization under the influence ofsodium methyl ester sulfonate (SMES) and castor oil. SMESand castor oil are respectively anionic and nonionic materials that are locally available, environmentally friendly and possess potential demulsifying properties such as interfacial film forming.